Safety and efficacy of l‐glutamine produced using Corynebacterium glutamicum NITE BP‐02524 for all animal species. (30th April 2020) - ,; Bampidis, Vasileios; Azimonti, Giovanna; de Lourdes Bastos, Maria; Christensen, Henrik; Dusemund, Birgit; Kos Durjava, Mojca; Kouba, Maryline; López‐Alonso, Marta; López Puente, Secundino; Marcon, Francesca; Mayo, Baltasar; et al.
Abstract: Following a request from the European Commission, the Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) was asked to deliver a scientific opinion on the safety and efficacy of l ‐glutamine (≥ 98.0%) produced by fermentation using a genetically modified strain of Corynebacterium glutamicum (NITE BP‐02524). It is intended to be used in feed for all animal species and categories as nutritional additive (amino acid) and as sensory additive (flavouring compound). Viable cells of the production strain and its recombinant DNA were not detected in the additive. l ‐Glutamine manufactured by fermentation using C. glutamicum NITE BP‐02524 does not give rise to any safety concern with regard to the genetic modification of the production strain. The use of l ‐glutamine produced by fermentation using C. glutamicum NITE BP‐02524 in animal nutrition is considered safe for all animal species when applied as a nutritional additive to achieve an adequate amino acid profile in feed and to overcome potential glutamine shortages during critical periods of life. The proposed use level (25 mg/kg feed) when used as sensory additive (flavouring compound) is safe for all animal species. The uses of l ‐glutamine produced using C. glutamicum NITE BP‐02524 as nutritional additive or as flavouring compound are considered safe for the consumer. l ‐Glutamine produced using C. glutamicum NITE BP‐02524 is not toxic by inhalation, is non‐irritant to skin and eyes and is not a skin sensitiser. l ‐Glutamine produced using C. glutamicum NITE BP‐02524 is considered safe for the environment. l ‐glutamine is a non‐essential amino acid and it plays a physiological role as such. Recent evidence shows that glutamine may act as conditionally essential amino acid mainly in growing animals and has some specific effects e.g. in improving intestinal development and immune response. This amino acid produced by fermentation using C. glutamicum NITE BP‐02524 is regarded as an efficacious source of glutamine for all animal species. For supplemental l ‐glutamine to be as efficacious in ruminants as in non‐ruminants, it would require protection against degradation in the rumen. The use of l ‐glutamine as sensory additive at 25 mg/kg feed is considered efficacious.